Biomass models to estimate carbon stocks for hardwood tree species - Ruiz-Peinado Gertrudix, R; Montero, G; del Rio, M (Forest Systems; Vol 21, No 1 (2012), 2012)
To estimate forest carbon pools from forest inventories it is necessary to have biomass models or biomass expansion factors. In this study, tree biomass models were developed for the main hardwood forest species in Spain: Alnus glutinosa , Castanea sativa , Ceratonia siliqua , Eucalyptus globulus , Fagus sylvatica , Fraxinus angustifolia , Olea europaea var. sylvestris , Populus x euramericana , Quercus canariensis , Quercus faginea , Quercus ilex , Quercus pyrenaica and Quercus suber . Different tree biomass components were considered: stem with bark, branches of different sizes, above and belowground biomass. For each species, a system of equations was fitted using seemingly unrelated regression, fulfilling the additivity property between biomass components. Diameter and total height were explored as independent variables. All models included tree diameter whereas for the majority of species, total height was only considered in the stem biomass models and in some of the branch models. The comparison of the new biomass models with previous models fitted separately for each tree component indicated an improvement in the accuracy of the models. A mean reduction of 20% in the root mean square error and a mean increase in the model efficiency of 7% in comparison with recently published models. So, the fitted models allow estimating more accurately the biomass stock in hardwood species from the Spanish National Forest Inventory data.
Keywords: aboveground biomass; additivity; belowground biomass; biomass models; Carbon Sequestration; hardwood species

Contribution of cork oak plantations installed after 1990 in Portugal to the Kyoto commitments and to the landowners economy - Coelho, Marta Baptista; Paulo, Joana Amaral; Palma, João Henrique Nunes; Tomé, Margarida (Forest Policy and Economics, 2012)
Cork oak stands are a part of the agroforestry ecosystem in Portugal, characterized by a low crown cover from cork oak trees, managed towards cork production, and sometimes in combination with grazing. In recent years, European Union policies gave impetus to a large area of new cork oak plantations, which have been established mainly for cork production purposes, and consequently with higher stand density than traditional agroforestry systems. These plantations are important not only for cork production but also for the carbon sequestered by these slow growing forests that won't be harvested for wood production. Thinning operations will be needed to avoid excessive inter-tree competition and wood extracted from these thinning may also provide income for the owners. In the present study, carbon sequestered and wood volumes resulting from thinning were estimated for the next 70 years. Three scenarios of different annual afforestation rates and different site indexes were tested. The resulting values for the considered scenarios show that, if the plantation rates are maintained, new cork oak plantations will have an important contribution to the Portuguese commitments to providing CO2 offsets under the Kyoto protocol. Additionally, due to the increasing values of initial density in new cork plantations, cork oak forests will produce a signiﬁcant volume of wood that may become an important contribution to the landowners' income.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Carbon Sequestration; Cork oak; Kyoto protocol; New plantations area; Wood

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Carbon sequestration with reforestations and biodiversity-scenic values - Caparros, A.; Cerdá, E.; Ovando, P.; Campos, P. (Environmental and Resource Economics, 2010)
This paper presents an optimal control model to analyze reforestations with two different species, including commercial values, carbon sequestration and biodiversity or scenic values. We solve the model qualitatively with general functions and discuss the implications of partial or total internalization of environmental values, showing that internalizing only carbon sequestration may have negative impacts on biodiversityscenic values. To evaluate the practical relevance, we compare reforestations in the South-west of Spain with cork-oaks (a slow growing native species) and with eucalyptus (a fast growing alien species). We do the analysis with two different carbon crediting methods: the Carbon Flow Method and the Ton Year Accounting Method. With the .first method forest surface increases more, but using mainly eucalyptus. With the second, additional reforestations are done mainly using cork-oaks. We value the impact on visitors of these reforestations using stated preferences methods, showing that when these values are internalized cork-oaks are favored.
Keywords: Biodiversity; Carbon Accounting; Carbon Sequestration; Forests; Optimal Control; Scenic; Stated Preferences

Forest humus forms as potential indicators of soil carbon storage in Mediterranean environments - Andreetta, Anna; Ciampalini, Rossano; Moretti, Pierpaolo; Vingiani, Simona; Poggio, Giorgio; Matteucci, Giorgio; Tescari, Francesca; Carnicelli, Stefano (Biology and Fertility of Soils, 2010)
The aim of this work was to investigate the potential of forest humus forms as indicators of soil C storage. To this purpose, Mediterranean forest soils in Southern and Central Italy were examined. Sites differed for elevation, climate, parent material and vegetation conditions, while summer drought was the common ecological factor. A morpho-functional criterion, based on holorganic layers thickness and A horizon properties, was used to classify humus forms, which ranged from Dysmoder to Eumull. Such variability allowed understanding of factors influencing organic matter storage. The relations between carbon stock and humus form were investigated for the topsoil layer (0–20 cm), which was supposed to contain the soil C pools most sensitive to climate change. We found that humus forms can be grouped in statistically different populations, with respect to topsoil C stocks. The use of A horizon structure was the main diagnostic criterion and represented the most effective approach to humus classification in Mediterranean conditions. It appears that humus forms have a clear potential as indicators of organic carbon status in Mediterranean forest soils.
Keywords: carbon pools; Carbon Sequestration; humus forms; Mediterranean forests; stabilization

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
The following values have no corresponding Zotero field: periodical: Handbook Of Operations Research In Natural Resources electronic-resource-num: 10.1007/978-0-387-71815-6
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Carbon sequestration by Quercus ilex L. and Quercus pubescens Willd. and their contribution to decreasing air temperature in Rome - Gratani, Loretta; Varone, Laura (Urban Ecosystems, 2006)
Carbon sequestration capability by Quercus ilex L and Quercus pubescens Willd., widely distributed in the city of Rome, and their contribution to decreasing air temperature were investigated. Crown volume is the most signiﬁcant (p < 0.01) variable explaining variation of air temperature below the tree crown. Q. pubescens gives a higher contribution to decreasing air temperature during the hottest months, due to its inherent larger crown volume than Q. ilex (252 ± 19 and 533 ± 52 m3 , respectively for the large size). Moreover, our results show the existence of a strong urban carbon dioxide dome with a peak CO2 concentration (on an average 432 ± 37 ppm) at polluted sites, 16% greater than at control sites. Total carbon sequestration is 84 ± 12 and 111 ± 9 Kg year−1 of CO2 for the small Q. ilex and Q. pubescens tree size,respectively, and 151 ± 10 and 185 ± 7 Kg year−1 of CO2 for the large Q. ilex and Q. pubescen tree size, respectively. Q. pubescens, by its higher total photosynthetic leaf surface area (39% higher than Q. ilex) and its higher mean yearly photosynthetic rates (48% higher than Q. ilex) seems to have a greater role than Q. ilex. However, taking into account the leaf longevity (i.e. 12 ± 3 months for Q. ilex and 4 ± 2 months for Q. pubescens), the evergreen species, by its continuous photosynthetic activity, contributes to reduce CO2 throughout the year, and in particular during the winter months, when trafﬁc volume has a pick, than Q. pubescens.
Keywords: Carbon Sequestration; evergreen and Deciduous species; heat island; lai; tree structure

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; INNES, JOHN L. (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
The following values have no corresponding Zotero field: publisher: Cambridge University Press
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; Innes, John L (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress